Early Decrease in Respiration and Uncoupling Event Independent of Cytochrome c Release in PC12 Cells Undergoing Apoptosis. (16th May 2012) - Berghella, Libera; Ferraro, Elisabetta
Abstract : Cytochrome c is a key molecule in mitochondria-mediated apoptosis. It also plays a pivotal role in cell respiration. The switch between these two functions occurs at the moment of its release from mitochondria. This process is therefore extremely relevant for the fate of the cell. Since cytochrome c mediates respiration, we studied the changes in respiratory chain activity during the early stages of apoptosis in order to contribute to unravel the mechanisms of cytochrome c release. We found that, during staurosporine (STS)- induced apoptosis in PC12 cells, respiration is affected before the release of cytochrome c, as shown by a decrease in the endogenous uncoupled respiration and an uncoupling event, both occurring independently of cytochrome c release. The decline in the uncoupled respiration occurs also upon Bcl-2 overexpression (which inhibits cytochrome c release), while the uncoupling event is inhibited by Bcl-2. We also observed that the first stage of nuclear condensation during STS-induced apoptosis does not depend on the release of cytochrome c into the cytosol and is a reversibile event. These findings may contribute to understand the mechanisms affecting mitochondria during the early stages of apoptosis and priming them for the release of apoptogenic factors.